2001
DOI: 10.1007/bf02722022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with bronchial asthma in school going children of rural Haryana

Abstract: Bronchial asthma is one of the most common illnesses in children. Factors influencing development of asthma have not been studied in rural population. 2000 school going children from five schools of Chhainsa and Dayalpur Primary Health Centre area in Ballabgarh Block of Haryana state were screened for presence of symptoms of asthma using a questionnaire suggested by International Study of Asthma and Allergy in Children (ISSAC). 40 children were identified as cases of bronchial asthma. For each child with asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
5
29
2
Order By: Relevance
“…Similar findings has been reported in the study by Dhabadi et al 6 History of cough without cold was strongly associated with asthma by both multivariate and univariate analysis, which shows similarities with other studies. 4,16,19 Other studies have also shown association of asthma with passive smoking, pets at home, environmental tobacco smoke, absence of smoke outlet 10,13,16,21 which has not been found statistically significant in this study. Around 50% of the asthmatics have limited sporting activity as well as activity at home, this shows poor control of asthma incapacitating to children.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Similar findings has been reported in the study by Dhabadi et al 6 History of cough without cold was strongly associated with asthma by both multivariate and univariate analysis, which shows similarities with other studies. 4,16,19 Other studies have also shown association of asthma with passive smoking, pets at home, environmental tobacco smoke, absence of smoke outlet 10,13,16,21 which has not been found statistically significant in this study. Around 50% of the asthmatics have limited sporting activity as well as activity at home, this shows poor control of asthma incapacitating to children.…”
Section: Discussioncontrasting
confidence: 59%
“…Similar are the prevalence rates of asthma in school children in the study quoted by Chhabra et al 11 (15.7%) and in an another study by Mistry 17 ( 12.5%). Various studies on asthma in school children show variation in prevalence in rural and urban areas, 4,6,10,14,15,18,19 the prevalence being higher in urban children. This may be due to urban air pollution because of industries, automobiles, allergens etc.…”
Section: Discussionmentioning
confidence: 99%
“…It is high as compared to other studies 7,8 , nasal obstruction, sneezing and cough had similar frequency in allergic rhinitis in this study while in bronchial asthma cough and wheezing were present in all patients followed by nasal obstruction and dyspnea. Among all the clinical findings, symptoms contribute more than signs for the diagnosis.…”
Section: Discussionsupporting
confidence: 45%
“…Among other risk factors like food allergy and pet animal have less contribution for allergic respiratory disorder accounting for 23% and 24% respectively which is still higher when compared to other studies done by 7 (6% and 12%). But allergy to pet animal is less as compared to study 8 (35.4%).…”
Section: Discussionmentioning
confidence: 64%
“…As such, the use of these fuels is considered to be a major risk factor for lung cancer as well as for cardiovascular and noncommunicable respiratory diseases such as chronic obstructive pulmonary disease and asthma (9,(24)(25)(26)(27)(28) and other respiratory diseases such as acute respiratory infections (20), chronic bronchitis (21,(29)(30), chronic obstructive pulmonary disease (31,32), and tuberculosis (33,34). Poor ventilation in kitchens may worsen the adverse health effects of asthma (35)(36)(37)(38)(39)(40). Findings from India's third National Family Health Survey (NFHS- 3,[2005][2006] showed that 90% of rural and 32% of urban households (all India total is 71%) in India use biomass and solid cooking fuels that generate smoke and unhealthy conditions when inhaled (41).…”
Section: Introductionmentioning
confidence: 99%